60.6k views
4 votes
Solve This
*SHOW WORK*

Solve This *SHOW WORK*-example-1
User Semih Eker
by
5.2k points

2 Answers

4 votes
First, solve the numerator:
6+3^2*(4)
3^2=9 so 6+9*4=42 because of 9*4=36

so for the fraction is 42/7 which equals 6.
6-1=5 so therefore

Y = 5

User Taulant
by
4.8k points
2 votes
Hey!
So you want to used PEMDAS and need to solve the numerator first.
so 3^2 is 9.
6+9*4 / 7. - 1
now multiply 9 and 4 and add 6
42/7 - 1
Now you want to divide first before you subtract again because of pemdas
Now you have 6 - 1 = y left
the answer is y = 5
Hope this helps!


User Machineghost
by
5.0k points